A new parafocusing paradigm for X-ray diffraction - Prokopiou, Danae; McGovern, James; Davies, Gareth; Godber, Simon; Evans, Paul; Dicken, Anthony; Rogers, Keith (International Union of Crystallography, 2020)
A new approach to parafocusing X-ray diffraction implemented with an annular incident beam is demonstrated for the first time. The method exploits an elliptical specimen path on a flat sample to produce relatively high intensity maxima that can be measured with a point detector. It is shown that the flat-specimen approximation tolerated by conventional Bragg–Brentano geometries is not required. A theoretical framework, simulations and experimental results for both angular- and energy-dispersive measurement modes are presented and the scattering signatures compared with data obtained with a conventional pencil-beam arrangement.
Keywords: focal construct geometry; powder X-ray diffraction; Bragg–Brentano geometry; conical incident beams